2020
DOI: 10.3390/ijerph17010343
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi and Workplace Wellness for Health Care Workers: A Systematic Review

Abstract: Several studies show the positive effects of new non-medical therapies known as complementary and alternative medicines (CAMs). In this context, the discipline of tai chi is obtaining a wider consensus because of its many beneficial effects both on the human body and mind. The aim of this study was to perform a systematic review of the scientific literature concerning the relationship between tai chi practice and wellness of health care workers (HCW) in their professional setting. The research was performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 26 publications
1
20
0
6
Order By: Relevance
“…From the 210 SRs of Tai Chi, 47 SRs were selected for the nal evidence synthesis and 114 estimates of effect, representing 59,306 adult participants in randomised controlled trials, were extracted from 37 SRs. Estimates of effects were not extracted and the GRADE-certainty of the evidence was not appraised for four SRs with unreliable meta-analyses [64,75,77,98] and six SRs with no meta-analysis [59,62,68,71,88,94]. No results were extracted from, nor was the AMSTAR-2 quality formally appraised or reported for 163 SRs (164 articles) because for 79 SRs a far more recent SR, typically with more primary studies was identi ed; for 46 SRs (47 articles) following further consideration, a SR of higher quality and/or with more primary studies in the meta-analysis for the PCO was selected; and for 38 of the SRs that did not conduct a meta-analysis, the PCO were reported by a SR with a meta-analysis (Additional le 4).…”
Section: Study Selection For Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…From the 210 SRs of Tai Chi, 47 SRs were selected for the nal evidence synthesis and 114 estimates of effect, representing 59,306 adult participants in randomised controlled trials, were extracted from 37 SRs. Estimates of effects were not extracted and the GRADE-certainty of the evidence was not appraised for four SRs with unreliable meta-analyses [64,75,77,98] and six SRs with no meta-analysis [59,62,68,71,88,94]. No results were extracted from, nor was the AMSTAR-2 quality formally appraised or reported for 163 SRs (164 articles) because for 79 SRs a far more recent SR, typically with more primary studies was identi ed; for 46 SRs (47 articles) following further consideration, a SR of higher quality and/or with more primary studies in the meta-analysis for the PCO was selected; and for 38 of the SRs that did not conduct a meta-analysis, the PCO were reported by a SR with a meta-analysis (Additional le 4).…”
Section: Study Selection For Evidence Synthesismentioning
confidence: 99%
“…General health, quality of life and wellbeing While most SRs were for adults and older adults with chronic diseases, a SR with no meta-analysis reported various physical and psychological bene ts of Tai Chi for students in higher education [94]. Another SR with no meta-analysis reported improved workplace productivity/motivation and work-related stress for healthcare workers [62].…”
Section: Adverse Eventsmentioning
confidence: 99%
“…For instance, while considerable literature contrasts specifically "good" and "bad" collaborations both in principle and in practice (Coetzee, 2019;Hoekman et al, 2010;Intriligator, 1990;Jermann et al, 2011;Lutomia, 2019;Madela, 2020;Moyi Okwaro & Geissler, 2015;Ordóñez-Matamoros et al, 2011), other literature describes "unpleasant" collaborations (Cocchiara et al, 2020;Youtie & Bozeman, 2016;Hajmohammad & Vachon, 2016;Kalinga, 2019;Mose, 2019;Musila, 2019;Omanga & Mainye, 2019). These latter reports comprise collaborative interactions that might repeat despite being unpleasant, in contrast to bad collaborative interactions that forestall any future work.…”
Section: Grounding Of Interactionsmentioning
confidence: 99%
“…These latter reports comprise collaborative interactions that might repeat despite being unpleasant, in contrast to bad collaborative interactions that forestall any future work. In these unpleasant scenarios-whether with co-authors (Youtie & Bozeman, 2016), co-workers (Cocchiara et al, 2020), or a supplier with a monopoly on materials needed for conducting a business (Hajmohammad & Vachon, 2016)-some circumstance in play may effectively force or require further interactions between partners despite past unfavorable ones, which suggests no small measure of domination at work in the partnership.…”
Section: Grounding Of Interactionsmentioning
confidence: 99%
“…A wide range of mind-body modalities designed to facilitate the mind's capacity to affect health has been used for a long time to improve mental health, well-being, quality of life, and physical health of clinical populations, and the general population in various occupations [6]. Previous studies have reported that mind-body modalities such as yoga [7], mindfulness-based interventions [8,9], and tai chi [10] can benefit the health of HCWs. Today, mind-body medicine has re-emerged for its mental health benefits in the context of COVID-19 [11,12], and some health systems use mind-body modalities to build strategies to improve the mental health of the public, patients with COVID-19, and HCWs [13,14].…”
Section: Introductionmentioning
confidence: 99%